STRATEGI KEBIJAKAN PENGGALIAN PENDAPATAN ASLI DAERAH - Anggoro, Damas Dwi; Alfandia, Nurlita Sukma (Profit: Jurnal Adminsitrasi Bisnis, 2018)
With the implementation of regional autonomy, the regions have the right to manage the finances of their respective regions and impose levies on the community in the form of taxes and regional retribution. Local Taxes and Local Levies are part of Regional Original Income (ROI). Local governments do not have fiscal independence so they are still very dependent on the portion of the Balancing Fund from the Central Government in financing regional expenditures. This research is expected to be able to find a strategy in the form of a policy of extracting local revenue which is considered the most appropriate. The descriptive qualitative approach with the type of descriptive research is used to be able to answer these problems. The results of this study state that the implementation of the ROI excavation policy in several research locations in Indonesia is in accordance with Law No. 28 of 2009. However, there are still limited areas in actively collecting taxes. The results of the SWOT analysis found six strategies for extracting local revenue, namely follow-up of collection actions, simplifying investment permits, conducting censuses and extending Local Tax Subjects, coordinating with related agencies, utilizing information technology for taxes and levies, improving service quality, assisting taxpayers and obligatory Retribution, and provision of technical guidance from the central government.Â